Mini review on dermatomycosis - Salwani, Ismail; Nor Iza, A.rahman; P.M., Ridzuan (2020)
Dermatomycosis is a fungal infection of the skin, hair, and nail caused by Trichophyton, Microsporum, and Epidermophyton. These organisms are found in the environment, humans, and animals in forms of yeast or mold. There are many factors that contribute to the growth of fungal infections in human body. But still majority of virulent factors and mechanisms of the diseases of fungi are not clear. This review paper describes types of fungal infections, their classification, epidemiology and new insights into pathogenesis with the focus on molecular mechanisms of the diseases. Furthermore, traditional and novel molecular diagnostic methods and the variety of drug treatment and the development of resistance against these drugs are discussed.